Cerenkov radiation: a multi-functional approach for biological sciences - Ma, Xiaowei; Wang, Jing; Cheng, Zhen (Frontiers in Physics, 2014)
Cerenkov radiation (CR) has been used in various biological research fields, which has aroused lots of attention in recent years. Combining optical imaging instruments and most of nuclear medicine imaging or radiotherapy probes, the CR was developed as a new imaging modality for biology studies, called Cerenkov luminescence imaging (CLI). On the other hand, it was novelly used as an internal excitation source to activate some fluorophores for energy transfer imaging. However, it also has some shortages such as relatively weak luminescence intensity and low penetration in tissue. Thus some scientific groups demonstrated to optimize the CLI and demonstrated it to three-dimension tomography. In this article, we elaborate on its principle, history, and applications and discuss a number of directions for technical improvements. Then concluded some advantages and shortages of CR and discuss some prospects of it.